Impact of teachers’ linguistic choices on ESL students’ verbal participation in selected secondary schools in Ekiti State, Nigeria - Deji-Afuye, Oladunni; Zhou, Sindiso (Journal for Language Teaching, 2025)
This study investigated the linguistic choices made by teachers and their effects on students’ verbal participation in English as a second language classroom interaction in selected secondary schools in Ekiti state in Nigeria. The study used a mixed methods approach and followed a case study as well as a descriptive research design. The approaches were triangulated to analyse extracts from 20 recorded classroom lessons and teacher interviews. The findings showed that the linguistic choices of teachers during classroom interactions significantly affected the classroom discourse structure and students’ verbal participation. The teachers’ linguistic choices were primarily made to accomplish the tasks of teaching the content and, as such, teachers were engaged mostly in initiating classroom exchanges, giving feedback, and keeping the interactions under control to the extent that students were mainly engaged to provide limited verbal responses to teacher initiations and directives. The study recommended teachers’ further professional training to enhance their discourse and pedagogical practices, provision of language teaching/learning resources and conducive classroom environments by the government. The development of applicable language policy and curriculum that facilitates rich classroom interactions and the development of student’s communication proficiency was also recommended to be the main focus of the Ministry of Education.